New k-phase materials, k-(ET) sub 2 Cu(N(CN) sub 2 )X: X = Cl, Br and I: The synthesis, structure and superconductivity above 11 K in the Cl ( Tc = 12. 8 K, 0. 3 kbar) and Br( Tc = 11. 6 K) salts - Wang, H. H.; Carlson, K. D.; Geiser, U.; Kini, A. M.; Schultz, A. J.; Williams, J. M.; Montgomery, L. K.; Kwok, W. K.; Welp, U.; Vandervoort, K. G.; Boryschuk, S. J.; Strieby Crouch, A. V.; et al. (Sandia National Laboratories, 1990)
The syntheses, structures, selected physical properties, and band electronic structures of three copper (I) dicyanamide halide salts of bis(ethylenedithio)tetrathiafulvalene ({kappa}-(ET)sub 2Cu(N(CN){sub 2})X, where X = Cl, Br, and I) are discussed. X-ray crystallographic studies demonstrate that the three derivatives are isostructural. The bromide salt is an ambient pressure superconductor with an inductive onset at 11.6 K and a resistive onset at 12.5 K. {kappa}-(ET)sub 2Cu(N(CN){sub 2})Cl exhibits the highest reported superconducting transition temperature (Tc = 12.8 K, 0.3 kbar) for an organic superconductor, once a semiconductor-semiconductor transition (42 K) is suppressed. The application of GE varnish or Apiezon N grease to crystals of {kappa}-(ET)sub 2Cu(N(CN){sub 2})Cl provides sufficient stress to induce superconductivity at ambient pressure.'' Crystals of the iodide remain metallic to {approximately}150 K, where they become weakly semiconductive. No sign of superconductivity was detected at pressures (hydrostatic and shearing) up to 5.2 kbar and at temperatures as low as 1.1 K. The band electronic structures of the three salts are essentially identical. The differences in superconducting properties are explained in terms of differences in lattice softness, which are strongly influenced by short C-Hhor ellipsisdonor and C-Hhor ellipsisanion contacts. 17 refs., 2 figs.